2017
DOI: 10.1177/1741134317737344
|View full text |Cite
|
Sign up to set email alerts
|

The pharmaceutical market and drug development prognosis in Japan: Current and future perspectives according to pharmacological classes

Abstract: Japan is now the second largest pharmaceutical market in the world. As a unique population, it provides many opportunities for pharmaceutical companies to develop their businesses. However, the market is strictly regulated by the government, and drug prices are determined according to the rules in Japan. Nevertheless, no detailed empirical analyses have been conducted to clarify what opportunities may exist for pharmaceutical companies in the future. In the present article, we reviewed the pros and cons of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Therefore, it has to be discussed along with drug pricing policy in Japan, since future directions in cancer therapy may easily change by regulatory frameworks. 34 In this context, this study revealed the prescription patterns of anticancer drugs in Japan, and these results can be a basis for future discussions to mitigate the impact of cancer care costs in Japan. Further work to investigate whether the identified prescription pattern is Japan-specific is needed.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, it has to be discussed along with drug pricing policy in Japan, since future directions in cancer therapy may easily change by regulatory frameworks. 34 In this context, this study revealed the prescription patterns of anticancer drugs in Japan, and these results can be a basis for future discussions to mitigate the impact of cancer care costs in Japan. Further work to investigate whether the identified prescription pattern is Japan-specific is needed.…”
Section: Discussionmentioning
confidence: 74%
“…Because of such high costs, there is a need to define the true value of a drug by evaluating its cost-effectiveness, an issue that, along with drug pricing policy, needs to be discussed, as the future direction of cancer therapy in Japan can be greatly affected by the regulatory framework. 33,34 The increase in prescriptions for generic drugs is a good indicator of the need to reduce the escalating costs of prescription drugs. In 2006, a new generic substitution policy was introduced to Japan under which pharmacists were allowed to substitute a brand name drug with a generic drug with the prescriber's permission.…”
Section: Atc Codementioning
confidence: 99%
“…Because of such high costs, there is a need to define the true value of a drug by evaluating its cost-effectiveness, an issue that, along with drug pricing policy, needs to be discussed, as the future direction of cancer therapy in Japan can be greatly affected by the regulatory framework. 33,34…”
Section: Pharmaceutical Market Trends: a Separate Analysis Of The Bramentioning
confidence: 99%
“…In 2014, Japan reportedly accounted for approximately 10% of global sales, which was the second largest share in the world. 1,2 Various differences have been reported between the current Japanese pharmaceutical market and markets of Western countries. The share of cardiovascular system drugs is relatively high among the top 100 drugs in the Japanese market, while that of antineoplastic and immunomodulating agents is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…3 Because the Japanese drug pricing system has encouraged R&D of new antineoplastic and immunomodulating agents and nervous system drugs that are likely to sell well in the Western market as well as the Japanese market, [4][5][6] the Japanese pharmaceutical market for these drugs is regarded as becoming similar to the markets of Western countries. 2 However, because the research focus on new molecular entities (NMEs) in Japan is limited, it is essential to discuss the prognosis of the Japanese pharmaceutical market.…”
Section: Introductionmentioning
confidence: 99%